Analisis Soft Skill Dan Hard Skill Siswa Dalam Mendukung Kebutuhan Industri 4.0 Di SMKN 2 Yogyakarta - Abdi Sakti Walenta; Ayu Hendra; Siti Nurqaidah; Destri Wahyuningsih; Andi Muh Akbar Saputra (Journal on Education, 2023)
Indonesia is one of the countries that has experienced industrial development to date. Education in Indonesia also experiences competition and challenges that are expected to balance the industrial era 4.0. The background of this research is the industry-based school education system implemented at SMKN 2 Yogyakarta during the industrial era 4.0. Therefore, this research is intended to find out how schools apply in improving students' soft skills and hard skills in the digital era at SMKN 2 Yogyakarta. The results of this research are expected to be useful for schools to improve the methods that have been implemented so that schools can be even better at honing their soft skills and hard skills. This type of research is a descriptive qualitative research. Collecting data using the method of observation, interviews, and documentation. The population in this study were school principals, heads of departmental programs (kaprog), teachers, and students. Data analysis was performed by transcript, coding, grouping, comparing, and contrasting. The results of this study indicate that: 1) SMKN 2 Yogyakarta has implemented several elements of soft skills which include: communication skills, thinking skills, problem identification skills, leadership, and conducting soft skill training. 2) Forms of increasing hard skills implemented at SMKN 2 Yogyakarta include: basic computer use and additional training in improving students' hard skills. 3) In the industrial era 4.0, SMKN 2 Yogyakarta has implemented: aligning the curriculum with the industrial world, completing facilities and infrastructure as much as possible, and preparing student human resources so they can balance in today's digital era.